Data Governance Practices in MENA : Case Study - Opportunities and Challenges in Morocco - World Bank (World Bank, Washington, DC, 2021)
Through successive royal speeches and digital transformation strategies, Morocco has identified the digital transformation of government, the economy, and society as high priorities for the country’s new development model and for strengthening the social contract between the state and citizens. This case study examines the data governance ecosystem in Morocco by applying a regional assessment tool developed the World Bank’s Middle East and North Africa (MENA) tech initiative. The case provides an assessment of existing practices to optimize the management and generation of data for development outcomes. Morocco has the opportunity to achieve its strategic digital transformation aspirations by reinforcing and effectively implementing a robust technical infrastructure and policy, legal, and regulatory framework for data governance to enable trusted data collection, processing, and (re)use by government, civil society, and the private sector. Enabling effective implementation of this data governance framework and better use by civil servants and individual users will also require investment to build institutional capacity and digital skills of all actors in the data ecosystem. Finally, an inclusive communications and dissemination campaign to increase public awareness and acceptance, can foster trust in data use in a country and region with a fragile social contract.